Health Impact Index. Development and Validation of a Method for Classifying Comorbid Disease Measured against Self-Reported Health. - Lorem, Geir F; Schirmer, Henrik; Emaus, Nina (PLOS ONE, 2016)
The objective of this study was to develop a method of classifying comorbid conditions that accounts for both the severity and joint effects of the diseases. The Tromsø Study is a cohort study with a longitudinal design utilizing a survey approach with physical examinations in the Tromsø municipality from 1974 to 2008, where in total 40051 subjects participated. We used Tromsø 4 as reference population and the Norwegian Institute of Public Health (FHI) panel as validation population. Ordinal regression was used to assess the effect of comorbid disease on Self-Reported Health (SRH). The model is controlled for interaction between diseases, mental health, age, and gender. The health impact index estimated levels of SRH. The comparison of predicted and observed SRH showed no significant differences. Spearman’s correlation showed that increasing levels of comorbidity were related to lower levels of SRH (RS = -0.36, p <.001). The Charlson Comorbidity Index (CCI) was also associated with SRH (r = -.25, p <.001). When focusing on only individuals with a comorbid disease, the relation between SRH and the Health Impact Index (HII) was strengthened (r = -.42, p <.001), while the association between SRH and CCI was attenuated (r = -.14, p <.001). CCI was designed to control for comorbid conditions when survival/ mortality is the outcome of interest but is inaccurate when the outcome is SRH. We conclude that HII should be used when SRH is not available, and well-being or quality of survival/life is the outcome of interest.